2014
DOI: 10.1111/gcb.12485
|View full text |Cite
|
Sign up to set email alerts
|

Can variable pH and low oxygen moderate ocean acidification outcomes for mussel larvae?

Abstract: Natural variation and changing climate in coastal oceans subject meroplanktonic organisms to broad ranges of pH and oxygen ([O2 ]) levels. In controlled-laboratory experiments we explored the interactive effects of pH, [O2 ], and semidiurnal pH fluctuations on the survivorship, development, and size of early life stages of two mytilid mussels, Mytilus californianus and M. galloprovincialis. Survivorship of larvae was unaffected by low pH, low [O2 ], or semidiurnal fluctuations for both mytilid species. Low pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 53 publications
1
112
0
Order By: Relevance
“…It is thus unclear whether pH and DO fluctuations primarily afford temporal relief from stressful conditions, or whether they compound environmental stress by requiring constant physiological adjustments. For larvae of two Californian mytilid mussels, Frieder et al's [31] study suggested the former, showing that constant low pH (7.48-7.51) during 8 days of exposure had a negative effect on development rate, whereas the fluctuating pH treatment (+0.15 pH units) was less detrimental. Keppel [33] recently observed that diel acidification cycles (pH 7.0-7.8 at control DO) severely reduced growth in oyster spat (Crassostrea virginica) only at low salinity conditions, whereas severe hypoxia cycles (0.5-7.2 mg l 21 at control pH) always reduced growth, and combinations of DO Â pH fluctuations elicited additive negative effects.…”
Section: A New Frontier: Effects Of Ph and Dissolved Oxygen Fluctuationsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is thus unclear whether pH and DO fluctuations primarily afford temporal relief from stressful conditions, or whether they compound environmental stress by requiring constant physiological adjustments. For larvae of two Californian mytilid mussels, Frieder et al's [31] study suggested the former, showing that constant low pH (7.48-7.51) during 8 days of exposure had a negative effect on development rate, whereas the fluctuating pH treatment (+0.15 pH units) was less detrimental. Keppel [33] recently observed that diel acidification cycles (pH 7.0-7.8 at control DO) severely reduced growth in oyster spat (Crassostrea virginica) only at low salinity conditions, whereas severe hypoxia cycles (0.5-7.2 mg l 21 at control pH) always reduced growth, and combinations of DO Â pH fluctuations elicited additive negative effects.…”
Section: A New Frontier: Effects Of Ph and Dissolved Oxygen Fluctuationsmentioning
confidence: 95%
“…Metabolism, survival and activity in adult Baltic blue mussels (Mytilus edulis trossulus) appeared to be robust even to severe acidification ( pH ¼ 7.5 and 7.0) and hypoxia (2.2 mg l 21 ), although the study was limited by short exposures and small sample sizes [30]. Similarly, concurrent low DO (2.8-3.3 mg l 21 ) Â low pH (7.61-7.68) had no effects on early-life survival and veliger size in two mussel species (Mytilus californianus, M. galloprovincialis, individual low DO, low pH treatments were not tested [31]). All three studies [29][30][31] argued that local adaptation of bivalves to regular low DO Â low pH conditions in the Baltic sea or the California upwelling region may partially explain these findings.…”
Section: (A) Molluscsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. californianus dominates the mid intertidal zone at the POA and TAY sites and has a high sensitivity to OA. OA conditions can reduce mussel larval size (Frieder et al, 2014;Kelly et al, 2015) as well as shell strength and thickness (Gaylord et al, 2011), which could have consequences for development time or predator avoidance (Gaylord et al, 2011). A reduction in the percent cover of M. californianus would have major implications for intertidal landscapes (Wootton et al, 2008), as mussels provide biogenic habitat for a diverse community of organisms (Smith et al, 2006).…”
Section: Rocky Intertidal Community Sensitivitymentioning
confidence: 99%
“…Since hypoxia can be persistent, or even permanent, as observed in many coastal and marine waters 225 worldwide (Helly and Levin, 2004;Diaz and Rosenberg, 2008), the survival of some calcifying organisms under persistent hypoxia suggests that they may have evolved the capacity to accommodate its impacts on energy metabolism and hence maintain calcification (Mukherjee et al, 2013;Frieder et al ,2014;Nardelli et al, 2014;Keppel et al, 2016). …”
mentioning
confidence: 99%